Hydration with Mannitol and Dextrose May Promote Cisplatin-Induced Nephrotoxicity: Test of Five Protocols of Hydration during Cisplatin Therapy in Rat Models. (4th October 2021) - Khosravi, Mohammad-Sedigh; Samimiat, Alireza; Mazaheri, Bahar; Ashrafi, Farzaneh; Talebi, Ardeshir; Nematbakhsh, Mehdi
Abstract : Backgrounds . Cisplatin (CP) still is a novel choice for solid tumor therapy, but it is accompanied with the side effect of nephrotoxicity. Hydration may reduce the risk of CP-induced nephrotoxicity, while the issue is still challenging. In this study, five types of hydration protocols including saline, mannitol, dextrose saline, saline plus furosemide, and saline plus mannitol were examined in both sexes of rats during CP therapy. Methods . Seventy-six male and female Wistar rats in 14 groups of experiments were subjected to CP therapy, and five types of hydration protocols were implemented, and the induced nephrotoxicity was evaluated via biochemical markers, kidney function parameters, and pathology investigation. Results . Male and female rats had different responses to hydration protocol types. The higher mortality rate was seen in female rats that received mannitol or dextrose hydration types. In addition, the serum levels of blood urea nitrogen (BUN) and creatinine (Cr) and sodium excretion fraction (ENa%) increased and the clearance of Cr (ClCr) decreased significantly (P < 0.05 ) in female rats hydrated with saline plus furosemide or mannitol plus saline-treated groups. The worsened condition in male rats is observed in the mannitol hydration group with a significant decrease of ClCr and significant increase of serum BUN and Cr and ENa% (P < 0.05 ). The higher kidney tissue damage score (KTDS) in the mentioned groups verified the findings. Conclusion . Hydration with mannitol or dextrose promotes the risk of nephrotoxicity during CP therapy with more intensity on the female.